Pretreatment With L-Citrulline Positively Affects the Mucosal Architecture and Permeability of the Small Intestine in a Murine Mucositis Model. (February 2016) - Antunes, Maísa Mota; Leocádio, Paola Caroline Lacerda; Teixeira, Lílian Gonçalves; Leonel, Alda Jusceline; Cara, Denise Carmona; Menezes, Gustavo Batista; Generoso, Simone de Vasconcelos; Cardoso, Valbert Nascimento; Alvarez-Leite, Jacqueline Isaura; Correia, Maria Isabel Toulson Davisson
Background: Mucositis is a common complication in patients undergoing radiotherapy and chemotherapy. It is associated with pain, poor quality of life, and malnutrition, leading to an increased number of hospital admissions and prolonged hospitalization. The use of immunonutrients may be an alternative treatment option, which may help to improve patient outcome. Objective : Here we assessed the impact of L-citrulline (CIT) on a murine model of 5-fluorouracil (5FU)–induced mucositis. Methods : Swiss male mice were randomized into 4 groups: control, CIT, 5FU, and 5FU+CIT. Mice were fed with commercial chow and supplemented with an oral solution of alanine (control and 5FU groups) or CIT (CIT and 5FU+CIT groups). On the seventh day, mice received intraperitoneal phosphate-buffered saline or 5FU (200 mg/kg, single dose) to induce mucositis. On the 10th day, mice were euthanized, and the blood and small intestines were harvested. Body weight, morphology, histopathology score (hematoxylin and eosin) of the small intestine (from 0–12), myeloperoxidase activity, oxidative stress level, and intestinal permeability were assessed. Results : We observed significant weight loss after the administration of 5FU in both treated and control animals. CIT administration contributed to a partial recovery of the mucosal architecture as well as an intermediate reduction of the histopathologic score, and functional intestinal permeability was partially rescued. Conclusions : CIT administration attenuated 5FU-mediated damage to the mucosal architecture of the small intestine, decreasing the size of the injured areas and promoting decreased intestinal permeability.